2020
DOI: 10.1177/2192568219876244
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Decompression Failure After Lateral Lumbar Interbody Fusion—Reported Failures and Predictive Factors: Systematic Review

Abstract: Background: In patients with symptomatic lumbar stenosis undergoing lateral transpsoas approach for lumbar interbody fusion (LLIF) surgery, it is not always clear when indirect decompression is sufficient in order to achieve symptom resolution. Indirect decompression failure (IDF), defined as “postoperative persistent symptoms of nerve compression with or without a second direct decompression surgery to reach adequate symptom resolution,” is not widely reported. This information, however, is critical to better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 32 publications
(94 reference statements)
2
13
1
Order By: Relevance
“…The number of operated levels, different fusion segments, and cage characteristics were also not the contributing factors to failure. These findings were consistent with previous literature [ 8 , 9 , 26 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The number of operated levels, different fusion segments, and cage characteristics were also not the contributing factors to failure. These findings were consistent with previous literature [ 8 , 9 , 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…In this study, we reported the rate of indirect decompression failure after applying our selection criteria to be as low as 6.8% which was relatively lower than those reported in previous studies [ 8 , 9 , 17 - 19 ]. All criteria were made of patient characteristics which all of them were nonmodifiable patient factors, so we believed that these factors would comprise a practical prerequisite for the procedure.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In a prospective randomized study [ 3 ], LLIF results in an increased foraminal area by 23% compared with 4.9% in MIS-TLIF on the approach side at three month follow-up. Kirnaz et al [ 35 ] recommended indirect decompression for patients who have symptomatic FS as long as we can confirm the source of the pain by eliciting radicular symptoms with a Kemp’s test. However, at present, there has been no research that looks at the efficacy of LLIF for patients only with radiculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent literature review, there was an overall incidence of indirect decompression failure of 9%. 6 Indirect decompression failure can be both related to patient factors (eg, concomitant central stenosis or lateral recess stenosis) and procedure factors such as cage dimensions or cage position. [7][8][9] To overcome this limitation, we modified the LLIF technique to include a minimally invasive tubular decompression (single-stage LLIF workflow [SSLLIF+]) in the same lateral position to treat concomitant pathology directly.…”
mentioning
confidence: 99%